Fungal Endophyte Alternaria tenuissima Can Affect Growth and Selenium Accumulation in Its Hyperaccumulator Host Astragalus bisulcatus - Lindblom, Stormy D.; Wangeline, Ami L.; Valdez Barillas, Jose R.; Devilbiss, Berthal; Fakra, Sirine C.; Pilon-Smits, Elizabeth A. H. (Frontiers in Plant Science, 2018)
Endophytes can enhance plant stress tolerance by promoting growth and affecting elemental accumulation, which may be useful in phytoremediation. In earlier studies, up to 35% elemental selenium (Se0) was found in Se hyperaccumulator Astragalus bisulcatus. Since Se0 can be produced by microbes, the plant Se0 was hypothesized to be microbe-derived. Here we characterize a fungal endophyte of A. bisulcatus named A2. It is common in seeds from natural seleniferous habitat containing 1,000-10,000 mg kg-1 Se. We identified A2 as Alternaria tenuissima via 18S rRNA sequence analysis and morphological characterization. X-ray microprobe analysis of A. bisulcatus seeds that did or did not harbor Alternaria, showed that both contained >90% organic seleno-compounds with C-Se-C configuration, likely methylselenocysteine and glutamyl-methylselenocysteine. The seed Se was concentrated in the embryo, not the seed coat. X-ray microprobe analysis of A2 in pure culture showed the fungus produced Se0 when supplied with selenite, but accumulated mainly organic C-Se-C compounds when supplied with selenate. A2 was completely resistant to selenate up to 300 mg L-1, moderately resistant to selenite (50% inhibition at ~50 mg Se L-1), but relatively sensitive to methylselenocysteine and to Se extracted from A. bisulcatus (50% inhibition at 25 mg Se L-1). Four-week old A. bisulcatus seedlings derived from surface-sterilized seeds containing endophytic Alternaria were up to 3-fold larger than seeds obtained from seeds not showing evidence of fungal colonization. When supplied with Se, the Alternaria-colonized seedlings had lower shoot Se and sulfur levels than seedlings from uncolonized seeds. In conclusion, A. tenuissima may contribute to the Se0 observed earlier in A. bisulcatus, and affect host growth and Se accumulation. A2 is sensitive to the Se levels found in its host’s tissues, but may avoid Se toxicity by occupying low-Se areas (seed coat, apoplast) and converting plant Se to non-toxic Se0. These findings illustrate the potential for hyperaccumulator endophytes to affect plant properties relevant for phytoremediation. Facultative endophytes may also be applicable in bioremediation and biofortification, owing to their capacity to turn toxic inorganic forms of Se into non-toxic or even beneficial, organic forms with anticarcinogenic properties.